Factors associated with pneumococcal vaccination in elderly people: a cross-sectional study among elderly club members in Miyakonojo City, Japan - Akihiro Sakamoto; Charnchudhi Chanyasanha; Dusit Sujirarat; Nobuhiro Matsumoto; Masamitsu Nakazato (BMC, 2018)
Abstract Background Pneumonia is the third leading cause of death in Japan. All elderly people aged 65 years or older are recommended to receive a pneumococcal vaccine. A subsidy for part of the cost of routine pneumococcal vaccination in this age group was introduced in 2014. Factors related to vaccination behavior among elderly adults have not been well reported. The purpose of this study was to investigate factors associated with vaccine uptake among elderly people in Japan. Methods We conducted a cross-sectional study, using a self-administered questionnaire among elderly club members aged 65 years or older in one city of Japan in April 2017. The participants were selected from among all elderly club members in the study area. Variables extracted from the questionnaire were analyzed using logistic regression analysis. Results A total of 208 elderly club members participated in the study. The mean age (± SD) was 77.2 (± 5.3) years. The pneumococcal vaccination rate was 53.2%. Logistic regression analysis revealed three variables that had a significant association with pneumococcal vaccination: a recommendation for vaccination from medical personnel (aOR 8.42, 95% CI 3.59-19.72, p <  0.001), receiving influenza vaccination in any of the previous three seasons (aOR 3.94, 95% CI 1.70-9.13, p = 0.001), and perception of the severity of pneumonia (aOR 1.23, 95% CI 1.03-1.48, p = 0.026). Conclusions Although the pneumococcal vaccination rate in this study was increased compared with previous reports, almost half of study participants had not yet received vaccination. Our findings could be helpful for developing vaccination strategies to increase the vaccine coverage in the elderly population.